Factors influencing muslims' intention to use e-wallet / Muhammad Sharizal Shafiq Mohd Shafiee - Mohd Shafiee, Muhammad Sharizal Shafiq (2020)
The integration of information technology and finance brings the development of E-wallet. In Malaysia, the government certainly wants to drive towards becoming a cashless society and become a leader in Islamic Digital Economy. Even though the transaction of e-money has increased over the years, the rate of adoption E-wallet by Muslims is still at a low rate. The study aimed to determine the factors influencing the Muslims’ intention to use E-wallet and investigate its relationship with the intention at the same this study intended to investigate its relationship with the intention as well as to examine the most influencing factor. This study applied quantitative research by distributing the questionnaire to collect data. Using the Technology Acceptance Model theory as the underlying theoretical base, the present study examined the influence of perceived ease of use, perceived usefulness, perceived security, social influence and trust towards the Muslims’ intention to adopt E-wallet. The study involved 394 respondents that responded to 420 questionnaires amongst Muslims in Shah Alam, Selangor. Frequency, descriptive, reliability, Pearson correlation and multiple regression analysis were used to analyse the collected data. The results of the study revealed that perceived ease of use, perceived usefulness, perceived security and trust had a positive and significant influence on the Muslims’ intention to use E-wallet. Based on the result, the paper recommends the E-wallet providers to organised many programs and attractive initiatives that relate to the E-wallet and implement proper education on E-wallet to all Muslims.